Analisis Tantangan Transformasi Peran Guru Dalam Pembelajaran di Era Digital - Anshar, Baktiar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Technological advancements and social changes have significantly transformed the landscape and paradigm of education. Modern education demands a transformation of teachers' strategic multifaceted roles in building a collaborative and inspirational learning culture in response to evolving learning needs and contemporary challenges. However, this transformation process faces various complex challenges. This study aims to analyze the challenges of transforming the teacher's role in the digital era, using a case study at SMA Negeri 9 Tana Toraja. This research employs a descriptive qualitative approach through in-depth interviews and observations. Data analysis was conducted thematically to identify patterns of challenges encountered. The results reveal several key challenges in the transformation of teachers' roles, such as gaps in media and digital literacy, shifts in mindset, and pedagogical competence. The findings also show that teachers with a strong change-oriented mindset tend to play adaptive roles and implement learning approaches that align with students' needs. The implications of this study highlight the importance of a holistic approach to supporting the transformation of the teacher's role through mindset shifts, improved media and digital literacy, enhanced pedagogical and technological competencies, and the strengthening of teacher learning communities as spaces for reflection and learning innovation, supported by inclusive school policies.